Risk Perception Analyst and Investment Literacy Level in the Decision to Become an Investor in the Capital Market - Kusnul Ciptanila Yuni K; Anita Musfiroh (JIES : Journal of Islamic Economics Studies, 2024)
The aim of this research is to analyze the risk perception and level of investment literacy in becoming an investor in the capital market study of GI BEI FE UNHASY investors. In this research, researchers used qualitative methods, with the type of field research. data collection technique, using in-depth interview techniques to collect data by asking questions to the interviewee. The data obtained were then analyzed. The research results show that risk perception and investment literacy have the potential to influence students' interest in becoming investors in the capital market.